How Efficient Are Banks in Hungary? - Molnar, Margit (OECD Publishing, 2011)
Apparent characteristics of the Hungarian banking market such as large profits and high margins suggest weak competitive pressures. Weak competition in turn, may reduce efficiency in a lack of pressures to converge to marginal cost and to stimulate managerial efforts to reduce X-inefficiency. Such conditions call for a gauging of efficiency of banks to better assess what is needed for a competitive and well-functioning banking system. Although the level of efficiency is only an indirect measure of competitive pressures, it may be superior to other ones available for international comparison. Concentration ratios are only a very imperfect measure, moreover, the Hungarian banking market structure with one larger and several somewhat smaller banks of similar sizes would suggest an even playing field. In fact, different market segments show very different degrees of concentration and several conditions for a competitive market are missing.
Keywords: Economics; Hungary